2019
DOI: 10.4103/eus.eus_35_19
|View full text |Cite
|
Sign up to set email alerts
|

Recognizing intrapancreatic accessory spleen via EUS: Interobserver variability

Abstract: Background and Objective:Accessory spleen (AS) may be encountered as an intrapancreatic lesion on EUS. This can look similar to other pancreatic pathologies and may lead to unnecessary interventions. The goal of this study was to evaluate the accuracy of EUS in distinguishing intrapancreatic AS (IPAS) from other pancreatic lesions.Materials and Methods:Twelve sets of endoscopic images of the spleen and various pancreatic lesions confirmed on histology or cytology were gathered. Ten endosonographers were asked … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…Rodriguez et al showed that an AS tends to be an isoechoic or hypoechoic mass with well-defined, smooth borders on EUS [ 73 ]. Kim et al reported that the IOR of determining whether or not the pancreatic lesion is IPAS is fair ( K = 0.37) [ 74 ] ( Table 4 ). They also reported that the sensitivity and specificity for IPAS were greater than 70%.…”
Section: Other Diseasesmentioning
confidence: 99%
“…Rodriguez et al showed that an AS tends to be an isoechoic or hypoechoic mass with well-defined, smooth borders on EUS [ 73 ]. Kim et al reported that the IOR of determining whether or not the pancreatic lesion is IPAS is fair ( K = 0.37) [ 74 ] ( Table 4 ). They also reported that the sensitivity and specificity for IPAS were greater than 70%.…”
Section: Other Diseasesmentioning
confidence: 99%
“…Presence of AS on imaging studies can mimic a neoplastic process 3,14,15 . Kim et al demonstrated only an overall fair interobserver agreement while identifying AS on imaging features alone 16 . The differential diagnosis includes a reactive lymph node, lymphoproliferative disorder, lymphoepithelial cyst, pancreatic neuroendocrine tumor (PanNET), solid pseudopapillary neoplasm (SPN), and acinar cell carcinoma (ACC).…”
Section: Discussionmentioning
confidence: 99%
“…Accessory spleens are located in the pancreatic tail in a significant minority of cases (5.5%) and can be particularly diagnostically challenging, with a high risk of misdiagnosis as hypervascular pancreatic tumours (Spencer et al 2010;Osher et al 2016;Vikse et al 2017;Ding et al 2018) leading to unnecessary biopsy procedures or surgery. Interobserver disagreement for diagnosis of intrapancreatic AS was found to be substantial with endoscopic US (Kim et al 2019). In particular, for diagnosis of AS in atypical locations (endoscopic), US-guided fine-needle aspiration biopsy (FNAB) may be useful (Tatsas et al 2012;Hocke et al 2013Hocke et al , 2017Gilani et al 2020).…”
Section: Accessory Spleen and Splenosismentioning
confidence: 99%